Pengaruh 3M (Menggambar, Merobek, Menempel) Terhadap Kemampuan Seni Rupa Pada Anak Usia 5-6 Tahun - Ibrahim, Firda H.; Ardini, Pupung Puspa; Laiya, Sri Wahyuningsi (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2024)
This study applied an experimental approach with 8 applications of mosaic media treatment. The study results indicated that the use of mosaic media had a positive effect in improving children's fine arts skills at TK Kembang Dahlia II Kindergarten. The study focused on a single group, administering the treatment over several days using mosaic media. The study involved 15 subjects, aged 5-6 years, comprising 7 boys and 8 girls. Based on the calculation results of respondents in the pre-test, there was an increase of 90%, and in the post-test, there was an increase of 203%. In conclusion, there is an improvement in the 3M (Menggambar, Merobek, Menempel) on children's fine arts ability. This is demonstrated by the increase between the pre-test and post-test. The pre-test data showed, after analysis, an average score of 14.53 for the children's fine arts ability. Meanwhile, after analysis, the post-test data showed an average score of 29.40 for the children's fine arts ability. This indicates that the respondents sampled in the study obtained results from the initial test to the final test.